Pengaruh Teknik Relaksasi terhadap Perubahan Status Mental Pasien Skizofrenia di Wilayah Kerja Puskesmas Limboto - Firmawati Firmawati; Ani Retni; Dian Putri Anggraini (Jurnal Pengabdian Bidang Kesehatan, 2024)
Patients with schizophrenia may experience an indirect social exclusion, leading those in their immediate vicinity to grow intolerably intolerant of their abnormal conduct and viewpoints. This can exarcebate mental health issues that may lead to relapses, so therapy is necessary, including the use of relaxation techniques such as guided imagert, The purposes of this study was to ascertain how relaxing methods affected the mental state shifts in the number of schizophrenia patients at the Limboto Health Center’s operational region. A single-group pre-post test design was used in this pre-experimental study, which included 88 schizophrenia patient in total. Purposive sampling was used to choose a total of 19 patients for the sample and the Wilcoxon statistical test was used to evaluate the data. According to the study findings, most schizophrenia patients (73.7%) had a severe mental state prior to receiving relaxation technique; afterward, most were classified as moderate (52.6%); the p-value was 0.000 (<α0.05). The Limboto Community Health Center’s working area’s schizophrenia patient’s mental status alterations were found to be influenced by relaxing techniques.